Can R&D-Inducing Green Tariffs Replace International Environmental Regulations? - Alireza Naghavi (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper investigates the link between trade and environment by exploring the effects of green tariffs on the location of firms, innovation and the environment. It shows that tariffs levied on polluting goods could result in less global pollution than harmonization of environmental standards by inducing more pollution abatement R&D, generating lower unit emissions from production, and reducing competition. Green tariffs reduce pollution by (1) shifting production to the region where environmental standards are respected, (2) strategically inducing abatement R&D by the Northern firm by granting the latter a higher market share, (3) creating abatement R&D by deterring delocation.
Keywords: F13; F18; F23; H23; Q21; R38; 330; Environmental Standards; Multinationals; Location of Firms; Pollution Abatement R&D; Green Tariffs; Umweltauflage; Ökosteuer; Zoll; Umwelttechnik; Multinationales Unternehmen; Betrieblicher Standort; Theorie